TRANSFORMASI KONFLIK INTERPERSONAL DALAM ORGANISASI SEKOLAH MELALUI KEPEMIMPINAN ADAPTIF KEPALA SEKOLAH:SYSTEMATIC LITERATURE REVIEW - Yullanda, Riva; Muhammad Akbar, Azan; Gistituati, Nurhizrah; Rusdinal; Nellitawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interpersonal conflict among teachers is a persistent challenge in school organizations that can undermine collaboration, reduce performance, and degrade educational service quality. Adaptive leadership by school principals is increasingly recognized as a strategic mechanism for transforming such conflict into opportunities for organizational growth. This study aims to synthesize existing empirical and theoretical literature on the role of adaptive leadership in managing and transforming interpersonal conflict in school settings. Using a Systematic Literature Review (SLR) approach, 23 articles published between 2020 and 2026 were identified and screened; 8 articles were selected for in-depth analysis based on relevance, methodological rigor and contextual alignment. The findings reveal that interpersonal conflict in schools predominantly stems from seniority culture tensions, divergent professional values, poor communication and resource inequity. Adaptive leadership practices diagnostic observation, open communication forums, teacher empowerment, collaborative culture cultivation, and humanistic leadership are consistently identified as effective in de escalating conflict and enhancing teacher motivation, collaboration and professionalism. Emotional intelligence competencies, particularly self-awareness, empathy, and self-management, further mediate the effectiveness of these adaptive strategies. This review concludes that the integration of adaptive and participative leadership models constitutes a comprehensive framework for conflict transformation in Indonesian elementary schools while highlighting the importance of contextualizing global theories within local sociocultural norms.